Representing death in rumi's when I Die from the perspective of systemic functional linguistics : A graduating paper submitted in partial of the Requirements for gaining the bachelor's Degree in English literatureL - Syifa Azzahra (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri, 2023)
et,1/Mumtaz c.1